Analisa Learning Loss (Ketertinggalan Pembelajaran) Yang Terjadi Di SDN Mrecah 1 Tanah Merah - Syaifullah Alramadhani; Priyono Tri Febrianto (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The learning and teaching process at SDN Mrecah 1 experienced a setback from the level of student understanding, because learning experienced changes and the teaching and learning process stopped at SDN Mrecah 1. This study uses qualitative research methods by using interview data collection techniques, observation, and documentation. This study uses descriptive data analysis techniques that aim to find out the learning loss events that occur at the school. The research results obtained from this study resulted that 4 out of class IV members experienced learning loss and the educators had made efforts and efforts to provide a way out of this incident. The conclusion from this study concludes that the pandemic has had a negative impact on fourth grade students at SDN Mrecah 1. As many as 4 fourth grade students at SDN Mrecah 1 have lost their skills in reading and speaking Indonesian fluently, and online learning is not suitable for application in grade IV SDN Mrecah 1.